2020
DOI: 10.1186/s12866-020-01849-w
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes associated with adaptive resistance to daptomycin in Streptococcus mitis-oralis

Abstract: Background Viridans group streptococci of the Streptococcus mitis-oralis subgroup are important endovascular pathogens. They can rapidly develop high-level and durable non-susceptibility to daptomycin both in vitro and in vivo upon exposure to daptomycin. Two consistent genetic adaptations associated with this phenotype (i.e., mutations in cdsA and pgsA) lead to the depletion of the phospholipids, phosphatidylglycerol and cardiolipin, from the bacterial membrane. Such alterations in phospholipid biosynthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…A number of phenotypic, metabolic and genotypic analyses have studied potential mechanisms involved in phenotypic DAP-R in S. mitis-oralis , most of which have utilized the same DAP-S/DAP-R strain pair described above [ 19 , 20 , 21 , 22 , 23 , 29 , 31 , 32 , 33 ]. These studies identified potential mechanistic themes relevant to the current findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of phenotypic, metabolic and genotypic analyses have studied potential mechanisms involved in phenotypic DAP-R in S. mitis-oralis , most of which have utilized the same DAP-S/DAP-R strain pair described above [ 19 , 20 , 21 , 22 , 23 , 29 , 31 , 32 , 33 ]. These studies identified potential mechanistic themes relevant to the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent metabolomic analyses of the current DAP-S/DAP-R S. mitis-oralis strain-pair also divulged interesting distinctions [ 22 ]. S .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations